2011
DOI: 10.1097/pep.0b013e3182099192
|View full text |Cite
|
Sign up to set email alerts
|

Normal Values of Functional Reach and Lateral Reach Tests in Indian School Children

Abstract: Normal mean values of FR and LR range from 22.7 cm to 37 cm and 16.3 cm to 22.5 cm, respectively. Height significantly correlates with both FR and LR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 18 publications
2
26
0
Order By: Relevance
“…A total of 14 functional balance tests were identified that were investigated in children . These measurement tools were categorized as single balance measures or batteries of balance tests, and subsequently organized according to the conceptual framework we defined in the introduction (Table ). Eight single balance measures and six batteries of balance tests were identified.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of 14 functional balance tests were identified that were investigated in children . These measurement tools were categorized as single balance measures or batteries of balance tests, and subsequently organized according to the conceptual framework we defined in the introduction (Table ). Eight single balance measures and six batteries of balance tests were identified.…”
Section: Resultsmentioning
confidence: 99%
“…These measurement tools were categorized as single balance measures or batteries of balance tests, and subsequently organized according to the conceptual framework we defined in the introduction (Table ). Eight single balance measures and six batteries of balance tests were identified. A detailed description of the test modalities for each test is available in Appendix S1 (supporting information published online).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Habib et al evaluated the balance abilities in Pakistani children using functional reach test [33]. Deshmukh et al have established normal values for functional and lateral reach in Indian school children [34]. However, reliability of PRT in hearing-impaired children remains to be investigated.…”
Section: Introductionmentioning
confidence: 98%